Micro-Targeting, Macro-Effects: Re-evaluating Political Communication in the Data Era - Prasetya Yoga Santoso (Global Writing Academica Researching and Publishing, 2024)
Digital transformation has transformed the political campaign landscape from a mass approach to a personalized one through the use of big data. This study aims to explore and analyze in depth the effectiveness of micro-targeting advertising as a political communication medium in the digital era. Using a qualitative approach with descriptive content analysis and literature review, this study relies entirely on secondary data sources derived from digital platform advertising transparency reports, election regulatory documents, and related scientific literature. The results indicate that operationally, micro-targeting advertising has high persuasive effectiveness in reaching swing voters due to the ability of personalized messages to penetrate internet users' attention spans through the use of big data and experimental advertising trials. However, from a sociopolitical perspective, this electoral effectiveness has negative impacts in the form of fragmentation of the digital public sphere through the creation of echo chambers and filter bubbles, which exacerbate social polarization. Furthermore, the hidden nature of advertising (dark ads) raises ethical issues related to the violation of user privacy and indicates a wide regulatory gap in the oversight of digital election governance. This study recommends the need for regulatory reforms that require full transparency in digital platforms' political advertising repositories and strengthen digital literacy among civil society.